SPIRITUAL AND MORAL SAFETY OF THE RUSSIAN YOUTH: SOCIOLOGICAL ANALYSIS OF MAJOR THREATS - Gafiatulina, N H (History, Archeology and Ethnography of the Caucasus, 2017)
The article covers the problem of sociological analysis of major threats to spiritual and moral safety of young people. The study of this problem involves theoretical comprehension of the scientific experience of research of socio-cultural and spiritual identity of the Russian society, preserving and reproducing its unique, unrivaled and inimitable type of morality and spirituality. Spiritual and moral safety of Russian young people is linked to the state of spiritual and moral sphere, the level of development of public culture and youth subculture. Young people are guarantors of spiritual welfare of the society and real potential of the changes that make up the vector of development of the Russian society, but due to age peculiarities they are very vulnerable and dependent on the changes in conditions of their integration into the available state of the society and on the existence of threats to spiritual and moral safety. In this context, the main challenges and threats to spiritual and moral safety of young people of modern Russia are the following: the collapse of the system of legal, social and moral regulation; socio-cultural split of monolithic culture and change of its homogeneous structure into a mosaic one; crisis of intergenerational relations; the ideological vacuum that was cultivated by communist ideology and the dismantlement of the system of agreement of opinion, which resulted from the collapse of communist ideology; massification of culture and its westernization; ideology of corruption and its downside is unrestrained consumption, imposed on young people as the highest moral value; insecurity of the majority of young Russians; socio-demographic crisis; institutional crisis and weakness of the socialization system; criminalization of behavior and consciousness of young generations of Russians; growth of social inequality and obvious, profound polarization of social strata of the Russian population; decrease in vitality, social feeling of the Russian population as a whole, and of young generations of Russia, in particular.